Regulatory frameworks for water resources management : a comparative study - Salman, Salman M. A., 1948-; Bradlow, Daniel D. (Washington, D.C. : World Bank, 2006)
This title examines how regulatory frameworks have addressed the various basic issues related to water resources management, and provides a comparative analysis of those issues. It elicits and discusses what it considers are the essential elements for a regulatory framework for water resources management, and identifies some emerging trends.
Includes bibliographical references (p. 177-188) and index.
oif 15/09/15
Loan
Keywords: Water resources development -- Law and legislation